Genetic Interaction between Rb and K-ras in the Control of Differentiation and Tumor Suppression - Takahashi, Chiaki (American Society for Microbiology, 2004)
Although the retinoblastoma protein (pRb) has been implicated in the processes of cellular differentiation, there is no compelling genetic or in vivo evidence that such activities contribute to pRb-mediated tumor suppression. Motivated by cell culture studies suggesting that Ras is a downstream effector of pRb in the control of differentiation, we have examined the tumor and developmental phenotypes of Rb and K-ras double-knockout mice. We find that heterozygosity for K-ras (i) rescued a unique subset of developmental defects that characterize Rb-deficient embryos by affecting differentiation but not proliferation and (ii) significantly enhanced the degree of differentiation of pituitary adenocarcinomas arising in Rb heterozygotes, leading to their prolonged survival. These observations suggest that Rb and K-ras function together in vivo, in the contexts of both embryonic and tumor development, and that the ability to affect differentiation is a major facet of the tumor suppressor function of pRb.